The South Bank Exhibition, London 1951: the viewpoint of The Architectural Review - Montes Serrano, Carlos; Lafuente Sánchez, Víctor; López Bragado, Daniel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
The Festival of Britain exhibition held in London in 1951 occupies a noteworthy place in the history of British architecture of the post-war period. This is because it constituted the starting point for the urban renewal of London’s South Bank. It was given strong support and great prominence by The Architectural Review, which published several articles and a monographic issue about it, in order to show how the master plan for the exhibition matched the ideals of Visual Planning and Townscape that the journal had been putting forward for some years previously. However, it was also the subject of criticism from a group of young architects, headed by Reyner Banham, who reacted to it by advocating an alternative style of architecture that was termed New Brutalism.
Keywords: London; Southbank; Exhibition; 1951